2010
DOI: 10.1002/psc.1255
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of [Tyr6]‐γ2‐MSH(6–12) on pain perception and in vivo hyperalgesic activity of its analogues

Abstract: [Tyr(6)]-gamma2-MSH(6-12) with a short effecting time of about 20 min is one of the most potent rMrgC receptor agonists. To possibly increase its potency and metabolic stability, a series of analogues were prepared by replacing the Tyr(6) residue with the non-canonical amino acids 3-(1-naphtyl)-L-alanine, 4-fluoro-L-phenylalanine, 4-methoxy-L-phenylalanine and 3-nitro-L-tyrosine. Dose-dependent nociceptive assays performed in conscious rats by intrathecal injection of the MSH peptides showed [Tyr(6)]-gamma2-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Intraplantar injections of the MRGPRC-specific peptides BAM8-22 or Tyr 6 -g 2 -MSH6-12 into juvenile or adult rats dose dependently resulted in acute nocifensive behavior, thermal hyperalgesia, and mechanical allodynia (Grazzini et al, 2004;Ndong et al, 2009). Likewise, intrathecal injection of MRGPRC agonists into juvenile or adult rats and Kunming mice also induced acute pain-like behavior and thermal hyperalgesia (Grazzini et al, 2004;Chang et al, 2009;Wei et al, 2010). MRGPRC may also be responsible for inflammatory pain, because complete Freund's adjuvant (CFA)-induced thermal hyperalgesia was alleviated by RNAi-mediated MRGPRC knockdown in rats (Ndong et al, 2009).…”
Section: Mas-related G Protein-coupled Receptors Bmentioning
confidence: 97%
See 2 more Smart Citations
“…Intraplantar injections of the MRGPRC-specific peptides BAM8-22 or Tyr 6 -g 2 -MSH6-12 into juvenile or adult rats dose dependently resulted in acute nocifensive behavior, thermal hyperalgesia, and mechanical allodynia (Grazzini et al, 2004;Ndong et al, 2009). Likewise, intrathecal injection of MRGPRC agonists into juvenile or adult rats and Kunming mice also induced acute pain-like behavior and thermal hyperalgesia (Grazzini et al, 2004;Chang et al, 2009;Wei et al, 2010). MRGPRC may also be responsible for inflammatory pain, because complete Freund's adjuvant (CFA)-induced thermal hyperalgesia was alleviated by RNAi-mediated MRGPRC knockdown in rats (Ndong et al, 2009).…”
Section: Mas-related G Protein-coupled Receptors Bmentioning
confidence: 97%
“…Notably, pain-enhancing effects of MRGPRC can only be assessed at low agonist doses (e.g., up to 20 nmol of Tyr 6 -g 2 -MSH6-12) and in a rigid time window of a maximum of 20 minutes postinjection (Wei et al, 2010). This low dose effect may be due to the activation of an analgesic off-target at higher peptide concentrations, most likely the Kyotorphin receptor, which masked MRGPRCinduced pain, whereas rapid peptide degradation may be responsible for the short-term response (Grazzini et al, 2004;Wei et al, 2010).…”
Section: Mas-related G Protein-coupled Receptors 581mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, elucidating the role of MrgprC in pain can contribute to a better understanding of the role of human MrgprX in pain, since there was no direct evidence that MrgprC had a modulatory effect on chronic inflammatory pain as an MrgprC-specific inhibitor had not been found yet. The current studies are limited to investigating the effect of different MrgprC agonists on pain and effects of MrgprC in the early stage of CFA models (24–48 h) [ 33 , 34 ]. These studies showed that intrathecal discontinuous injection of BAM8-22 could suppress thermal hyperalgesia in chronic inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%